Pengaruh Likuiditas Dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Perbankan Swasta Nasional Di Bursa Efek Indonesia Periode 2018-2021 - Sopian Efendi; I Nengah Arsana; Ni Nyoman Yuliati (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of liquidity and solvability on the profitability of national private banking companies on the IDX for the 2018-2021 period. This type of research is associative research. The population used was 35 National Private Banking companies listed on the Indonesia Stock Exchange (IDX), with a total sample of 20 companies taken using a purposive sampling method. This study uses quantitative data types with secondary data sources in the form of company financial report data. Data were analyzed using multiple linear regression analysis techniques, with hypothesis testing carried out through the t test. The results showed that: liquidity that proxied by cash ratio (CR) has a significant effect on profitability, with a value of -tstat (2.106) > -tα (1.992), liquidity that proxied by loan to deposit ratio (LDR) has no significant effect on profitability with -tstat (0.448) < -tα (1.992), solvability that proxied by debt to equity ratio (DER) has no significant effect on profitability with -tstat (1.511) < -tα (1.992); and (4) solvability that proxied by debt to asset ratio (DAR) has no significant effect on profitability with tstat (1.172) < tα (1.992).